Mozgovaia ataka . Mozgovaia ataka . Brain Attack . Мозговая атака - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the issues of disarmament and the use of nuclear weapons. Featured in the program: Osipov, IUrii (President of the Russian Academy of Sciences) Contributors: Mazheika, Kipras (Anchor) О разоружении и использовании ядерного оружия. В программе участвуют: Осипов, Юрий (Президент Российской академии наук) Создатели: Мажейка, Кипрас (Ведущий/Ведущая)